Optimalisasi Children Well-Being melalui Family Bonding Time pada Anak Usia Dini: Kajian Literatur - Dhea Mutiara Indah; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Family is the first and primary environment that plays a crucial role in shaping children’s holistic well-being. During early childhood, the quality of family interactions serves as a foundation for socio-emotional development, a sense of security, happiness, and school readiness. One important form of interaction that contributes to children's well-being is family bonding time, defined as quality time spent through meaningful shared activities between parents and children. This study aims to analyze the role of family bonding time in enhancing children’s well-being in early childhood through a literature review approach. Data were collected from reputable national journal articles, developmental theory books, and academic references related to secure attachment, parental involvement, and child well-being. The analysis employed a qualitative descriptive approach through literature identification, thematic categorization, synthesis of previous studies, and conceptual interpretation. The findings indicate that family bonding time contributes significantly to strengthening secure attachment, emotional regulation, social skills, language and cognitive development, as well as children’s sense of security and happiness. Furthermore, family togetherness functions as a protective factor against excessive gadget use and individualistic tendencies. The review also reveals that the quality of interaction has a greater impact on children’s well-being than the amount of time spent together. The implications of this study highlight the importance of strengthening parenting programs and family–school partnerships in early childhood education settings by integrating family bonding activities as a sustainable strategy to promote children’s holistic well-being and optimal development